The cytokine profile in obesity and asthma in children - A. A. Tarabrina; L. M. Ogorodova; Yu. G. Samoilova; S. V. Fedosenko; O. S. Fedorova; V. A. Petrov; D. V. Podchinenova; A. S. Boyko (Бюллетень сибирской медицины)
Background. Childhood obesity is one of the pressing problems in modern healthcare, since it is associated with a high risk of non-communicable diseases, such as bronchial asthma (BA). The aim. To determine the features of cytokine profiles in children with and without BA, depending on body weight and visceral fat area.Materials and methods. At the first stage, 506 Tomsk schoolchildren underwent anthropometry with the calculation of the body mass index (BMI) and measurement of the visceral fat area (VFA) using the InBody 770 analyzer. Fiftyone (51) children from the first stage were included in the second clinical and diagnostic stage. The children were divided into four clinical groups: “Obesity” (n = 17), “Visceral Obesity” (n = 7), “Asthma” (n = 15), and “Healthy Children” (n = 12). In all study participants, the levels of interleukin (IL)-6, IL-8, IL-4, IL-10, and immunoglobulin (Ig) E in the blood serum were determined by the multiplex assay (MagPix and Luminex 200 c analyzers). Statistical data analysis was carried out using the Statistica 10.0 software package and the 4.2.2 version of R.Results. The levels of IL-10 in the “Asthma” (p < 0.006) and “Obesity” (p < 0.008) groups were significantly higher than in the “Visceral Obesity” group. Significantly higher levels of IL-8 were found in patients with asthma (p < 0.003) and obesity (p < 0.003) compared to the “Visceral Obesity” group. Higher concentrations of IL-6 were found in the “Asthma” (p < 0.001) and “Obesity” (p < 0.028) groups compared to the “Visceral Obesity” group.Conclusion. Similar upward changes in IL-6, IL-8, and IL-10 in children with asthma and obesity without a history of asthma may explain the contribution of obesity to a risk of asthma in children, possibly through excessive production of these proinflammatory cytokines that contribute to the implementation of Th2-mediated allergic inflammation.